STRATEGI KOMUNIKASI PEMASARAN DIGITAL DALAM MENINGKATKAN KEPERCAYAAN KLIEN PADA PT. DRUZH WISATAWAN MANAJEMEN - Baiq Dilla Triana; Putu Suparna (Bajang Institute, 2025)
This study aims to analyze the digital marketing communication strategy implemented by PT Druzh Wisatawan Manajemen in building and enhancing client trust in its immigration consulting services. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation of digital marketing activities, and documentation of promotional content on Facebook and Instagram. The findings reveal that the company’s digital communication strategy focuses on providing informative and educational content related to visa procedures, immigration regulations, service requirements, and important announcements. This content plays a significant role in increasing client awareness and confidence in the company’s professionalism. Clients reported that clear, timely, and transparent information—especially regarding service processes and required documents—strengthens their trust in the company. However, challenges remain, including inconsistent response times, limited content variation, and the need for broader digital platform utilization. Overall, PT Druzh Wisatawan Manajemen’s digital marketing communication has positively contributed to building client trust, yet improvements in responsiveness, content development, and media diversification are necessary to optimize its effectiveness